Post-COVID-19 manifestations-are they a matter of concern? - Rajan, Deepak; Raheela, Ameena Subair; Muduvana, Preetha; Chirammal, Sachin Kuthirummal; Saraswathy, Anitha Subhadra; Choorickadu, Bhagyalakshmi; Purayi, Vismaya Pattarkatt Puthiya; Chelangara, Chathurya; Mullan, Akshay; Chandran, Akshay; Ariyeri, Shanil; Kandiyantavida, Lenin Thazhe (International Journal Of Community Medicine And Public Health, 2022)
Background: COVID-19 is an infectious disease caused by a new coronavirus (SARS CoV-2) which may seriously affect the respiratory system. Global data shows 80% of the patients suffer from mild symptoms such as fever, dry cough and fatigue. 87.4% of COVID-19 patients reported persistence of at least one symptom after recovery. The aim of the study was to estimate the prevalence of Post COVID-19 Manifestations (PCM) and its determinants among those declared positive for SARS-CoV-2 in Kannur district of Kerala. Methods: A cross-sectional study was carried out among COVID-19 recovered individuals who were tested positive for SARS-CoV-2 during the period from March 2020 to September 2020 in Kannur district. Study participants were contacted over phone and details collected were entered into Microsoft excel and analysed using Stata 14.4. Descriptive analysis, chi-square test and binary logistic regression were used to interpret the data. Results: The prevalence of PCMs among the study population was found to be 19.5%. The most common type of PCM reported was loss of taste. Major predictor variables of the outcome were symptom status during testing for COVID-19, hospital admission for COVID-19 treatment and excessive fatigue. Conclusions: The study found that PCMs occurred in about one-fifth of the study population. Considering the burden of PCMs among the study population, this study provides rationale for strengthening and sensitization of primary health care providers and the general public for the identification and management of PCMs.